SS31 Ameliorates Oxidative Stress via the Restoration of Autophagic Flux to Protect Aged Mice From Hind Limb Ischemia - Yang, Qiaoyun; Li, Chunqiu; Chen, Qingwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Oxidative stress and impaired autophagic flux play important roles in the development of peripheral artery disease (PAD). SS31 is considered an important antioxidant peptide and autophagy regulator. We aimed to investigate the role of SS31 in PAD myopathy and its possible mechanism both in vivo and in vitro. Methods: A hind limb ischemia (HLI) model was established with old C57BL/6 (14-month-old) mice. Mice in the SS31 group were intraperitoneally injected with SS31 (3 mg/kg) for 4 weeks. We examined skeletal muscle function and histomorphology, autophagy-related protein levels and reactive oxygen species (ROS) content. For the in vitro experiments, after C2C12 myotubes were treated with CoCl2, SS31, and chloroquine (CQ) or rapamycin (RAPA), we measured ROS content, autophagy-related protein levels and antioxidant enzyme expression. Results: SS31 treatment effectively enhanced the recovery of skeletal muscle function, alleviated skeletal muscle injury and suppressed mitochondrial ROS production in ischemic limbs. SS31 reduced apoptosis and oxidative stress, and SS31 restored impaired autophagic flux by inhibiting the Akt-mTOR pathway. In vitro studies showed that SS31 restored autophagic flux and improved oxidative stress in C2C12 cells. Moreover, phosphorylated Akt (p-Akt) and phosphorylated mTOR (p-mTOR) levels were reduced. Conclusions: These experiments indicated that SS31 can inhibit oxidative stress by restoring autophagic flux to reverse hypoxia-induced injury in vivo and in vitro.